Karakteristik Mekanik dan Estetika Beton dengan Material Limbah Batu Onyx sebagai Alternatif Agregat Kasar - Danang Hadi Nugroho; Aditya Purnama; Danang Wijanarko (Universitas Batanghari Jambi, 2026)
The high consumption of natural aggregates in concrete production has led to increased exploitation of natural resources, causing environmental degradation. At the same time, the natural stone industry, particularly Onyx stone processing, generates a significant amount of solid waste that has not been optimally utilized. This study aims to evaluate the effect of using Onyx stone waste as a partial substitution for coarse aggregate on the compressive strength of concrete cylinders and the aesthetic quality of concrete surfaces. A quantitative approach with a pure experimental method was employed. Concrete cylinder specimens with a diameter of 150 mm and a height of 300 mm were prepared with Onyx waste substitution levels of 0%, 10%, 20%, and 30%, with five specimens for each variation. Compressive strength testing was conducted at 28 days in accordance with SNI 1974:2011, while aesthetic aspects were evaluated through visual observation of the concrete surface. The results indicate that Onyx waste substitution of up to 10% does not cause a significant reduction in compressive strength compared to control concrete, with an average value of 28.16 MPa. However, substitutions of 20% and 30% result in statistically significant strength reductions. In terms of aesthetics, higher Onyx content enhances surface color variation and texture. Therefore, the use of Onyx stone waste is recommended as an alternative coarse aggregate up to a maximum level of 10% to achieve environmentally friendly concrete with adequate mechanical performance and improved aesthetic value.